Vietnamese and Australian rules of politeness and respect - Nguyen , Thanh Tung (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This research paper argues that in interpersonal communication interlocutors’ behaviours are governed by their systems of beliefs and values. Thus it examines the systems of beliefs, values, and behaviours of the Vietnamese and of Australian peoples. The two different systems of beliefs of the Vietnamese (Buddhism, Confucianism, and Taoism) and the Australians (Judeo-Christianity) lead to two distinctive systems of values of ±equality, ±independence, ±privacy, and ±assertiveness. In their turn, these values govern opposite behaviours in cross-cultural communication, which may cause communication breakdown. Therefore, cultural awareness and sensitivity should be a basis for overcoming communication problems likely to face people from countries with contrastive cultural patterns.